ANALISIS KONTROL LAMPU OPERASI MENGGUNAKAN SENSOR JARAK BERBASIS MIKROKONTROLER ARDUINO UNO - Khairil Abdillah; Muhammad Riduan (JURNAL MUTIARA ELEKTROMEDIK, 2021)
The operating lamp is one of the madical devices that has a very important role in the world of health, especially at The nimal:pain during surger. The purpose of this study was to determine the analysis of operating lamp control using a proximity sensor based on the Arduino Uno microcontroller, to determine the effect of distance to objects on operaring lamp devices. Adjust the distance between the object to the operating lampu so that the module will automatically assign a distance value according to the object to the operating lamp. The results obtained in this study are at a distance of 50 cm the light value to the object is 8023, at a distance of 100 cm the light value is obtained ot the object 2,827 at a distance of 140 cm, the value of light ot the object 1,298. the conclusion of this study is that the closer the distance to the operating lamp is to the object, the higher the intensity and vice versa because the series of readings of light and distance values automatically reads the distance and ligh values. Yes operating lights against objects.